Torque ripple and magnetic forces on teeth in IPM machines. Issue 5 (19th August 2014) - Wang, Kai; Zhu, Zi-Qiang; Ombach, G; Chlebosz, W; Sykulski, Jan; Masmoudi, Ahmed
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The purpose of this paper is to investigate torque ripple and magnetic force on the teeth in interior permanent magnet machines over a wide range of speed operation for electrical power steering applications. Design/methodology/approach The flux-weakening capability of interior permanent magnet machines has been analysed by finite element method considering the effect of cross-coupling between d- and q-axis current. The traditional method of analysing torque ripple is based on constant torque and flux-weakening region. However, the cross-coupling need to be considered when applying this technique to flux-weakening region. Meanwhile, the torque ripple with current amplitude and angle and with different speed in the flux-weakening region is also investigated. In addition, the magnetic force on the teeth due to the separated teeth with stator yoke is also investigated during the constant torque and flux-weakening region. Findings The torque ripple and magnetic force on teeth in IPM machine are dependent on current and current angle. Both the lowest torque ripple and magnetic force on teeth exist over the whole torque-speed region. Research limitations/implications The purely sinusoidal currents are applied in this analysis and the effects of harmonics in the current on torque ripple and magnetic force on teeth are not considered in this application. The 12-slot/10-pole IPM machine has been employed in this analysis, but this work can be continued to investigate different slot/pole number combinations. Originality/value This paper has analysed the torque ripple and magnetic force on the teeth in IPM machines for EPS application over a wide range of operation speed, which are the main cause of vibration and acoustic noise. The variation of torque ripple with current amplitude and angle as well as speed in the flux-weakening region is also investigated. In addition, the magnetic force on the teeth is also investigated over the whole torque-speed region.